A new species of Cintaroa from India and new records of Craspedophorus from Pakistan and the Philippines (Coleoptera: Carabidae: Panagaeini) - Häckel, Martin; Sciaky, Riccardo (Zootaxa, 2019)
The second species of the orophilous apterous genus Cintaroa Kasahara, 1989 (Carabidae, Panagaeini), C. sikkimica sp. nov. from Sikkim (Northern India) is here described. Checklists of Panagaeini Bonelli, 1810 from Pakistan and the Philippines are provided, presenting new records and discussions.